Changes in microbial and physicochemical properties under cover crop inclusion in a degraded common bean monoculture system - Aban, Carla Luciana; Perez Brandan, Carolina; Verdenelli, Romina Aylen; Huidobro, Dina Jorgelina; Meriles, José Manuel; Vargas Gil, Silvina (Elsevier, 2021)
The expansion of the common bean monoculture system along with intensive agricultural practices focused on productivity has generated a misuse of natural resources, accompanied by a significant decline of the soil ecosystem services. The aim of this study was to analyze the short-term effect (3 years) of the inclusion of different cover crops (legumes, non-legumes and mixtures) on the physicochemical, biological properties and crop yield in a degraded common bean monoculture system in the north region of Argentina. The inclusion of legumes (vetch and melilotus) and non-legumes (oat and wheat) as sole cover crops over three consecutive years significantly increased the abundance of the main microbial groups, microbial biomass C and N (MBC and MBN) and the activity of the common bean rhizosphere microbial community, which resulted into a fast improvement of soil quality and rhizosphere microbiota compared with bean monoculture. However, mixed cover crops (oat + vetch) had a positive but lower impact on rhizosphere microbial community abundance compared to legume or non-legume cover crops when used as sole cover crops. The information generated in this study will contribute to the evaluation of the inclusion of specific cover crops as a conservation strategy to recover soil health and minimize soil degradation, while maintaining crop yields.